Caribbean Report 15-03-1989 - Timmins, Jerry (anchor); Perry, Bill (interviewee); Caroit, Jean Michel (correspondent); Crosskill, Hugh (correspondent); Allen, C. Lloyd (interviewee); Allen, Neil (correspondent); Hagan, Pat (interviewee); Bennish, Peter (correspondent) (The British Broadcasting Corporation, 1989)
U.S. Trade Secretary, Bill Perry speaks on the Brady Plan to reduce the burden of debt in Latin American countries. Perry is of the view that Caribbean countries fall within the plan and should receive benefits. With a foreign debt of more than 3.7 billion dollars, Santo Domingo has the highest per capita debt ratio in the region. Despite protests against apartheid, the Jamaica Boxing Board is hosting the annual convention of the International Boxing Federation. In trade, the nutmeg cartel, Indonesia and Grenada is collapsing. The Indonesian Marketing Association is marketing its nutmeg directly and has cut its prices by over one thousand dollars a ton. At the Canadian enquiry into drug use by amateur athletes, Angela Taylor-Issajenko continues her testimony before the Commission.
1. Headlines (00:00-01:05)
2. Interview with U.S. Trade Secretary, Bill Perry on the Brady Plan to reduce the burden of debt in Latin American countries and speculation of assistance to Caribbean countries (01:06-03:58)
3. BBC Correspondent, Jean-Michel Caroit reports on the foreign debt in Santo Domingo, the highest per capita in the region (03:59-05:45)
4. Interview with C. Lloyd Allen, President of Jamaica Boxing Board and Neil Allen, British journalist on Jamaica Boxing Board's decision to host the annual convention of the International Boxing Federation (05:46-08:07)
Keywords: Debts, External -- Latin America.; Debts, External -- Caribbean Area.; Debts, External -- Dominican Republic.; Boxing -- Jamaica -- Congresses.; Apartheid.; Nutmeg industry -- Indonesia.; Nutmeg industry -- Grenada.; Price cutting -- Indonesia.; Cartels -- Grenada.; Cartels -- Indonesia.; Doping in sports -- Canada.; Sports -- Corrupt practices -- Canada.; Sports -- Drug use -- Canada.; U.S. Trade Secretary.; Indonesian Marketing Association.